PENGEMBANGAN SUPLEMEN BERBASIS PENDEKATAN SAINTIFIK PADA MATERI STRUKTUR ATOM - Pramesti Windu Anugraheni; Hairida Hairida; A Ifriany Harun (Universitas Muhammadiyah Pontianak, 2021)
This research aims to determine student responses to the supplements based on a scientific approach to the atomic structure material. Type of this research is Research and Development (R&D) by adapting the development steps by Borg & Gall model. The subject of this study was a supplement based on a scientific approach to the Atomic Structure Material which was tested on class X students at Taman Mulia Senior High School, SMA N 1 Sungai Raya and SMAS Indonesia Muda. Supplements based on a scientific approach to the atomic structure material received responses from students in the initial field responses test with excellent criteria (85,9%). And the main field response test with excellent criteria (90,4%). According to the students response test to the supplement based on a scientific approach to the Atomic Structure Material showed that the supplement was very feasible to be used as a learning suplement for Atomic Structure Material.